Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content1. The Awareness level of Students of the Education College in the State of Kuwait about the Digital Citizenship DimensionsMr. Abdulaziz Mutlaq Saad Al-Watari Al-Rashidi, Dr. Farah Abdulaziz Al-Mutawa2. The Extent of Awareness to Which the Academic Body and Students at the University of Nizwa Understand the Concept of Governance (Traditional and Electronic)Ms. Huda Mohammed Juma Attia, Dr. Radhia Sulaiman Nasser Al-Habsi3. Reality of female Islamic studies teachers promoting values of volunteer work among female secondary school students in MakkahProf. Hoba Ahmed Akram, Ms. Reem Mohammed Almontashri4. Transformational Leadership Among Government School Principals and Its Relationship  to Teachers' Professional Compatibility in The Governorate of South Al-Sharqiyah  in The Sultanate of OmanMr. Tariq Juma Al-Rasbi, Dr. Rabia Al-Mur Al-Dhuhli, Dr. Radhiya Sulaiman Al-Habsi, Dr. Yaqoob Salim Al-Thani5. The reality of the contributions of associations of people with disabilities  in achieving their social empowerment An applied study on care centers for persons with disabilities in the city of HailMs. Jawaher Ghazi Al-Ashqar6. Challenges of Implementing E-Learning in Upper Elementary Education: Perspectives of Abu Al-‘Arqan School Teachers, South HebronMs. Hiyam Yousssef Daraweesh, Dr. Ibrahim Mohammad Arman
Keywords: Journal of Educational and Psychological Sciences